Generation Z in the Cashless Era: An Analysis of Digital Financial Literacy and Consumption Behavior: Penelitian - Sinuhaji, Meutia Maryam; Keisha Maritza Azzahra; Muhammad Ariib Firaas3; Khalisha Azzahra Habibi; Karunia Ramadhan (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to analyze the relationship between digital financial literacy and Generation Z's consumption behavior in the cashless era. Technological advancements and cashless payment systems have driven significant changes in people's consumption patterns, especially among Generation Z, who are known as active users of digital financial services such as e-wallets, mobile banking, and QRIS. The research method used was quantitative descriptive, with data collection techniques through questionnaires distributed to 71 respondents. The results of the study show that Generation Z has a fairly good level of digital financial literacy from the technical aspect, but it is still low in financial management and financial risk awareness. The ease of transactions and digital promotions has been shown to encourage consumptive behavior, especially in individuals with low levels of financial literacy. Therefore, increasing digital financial literacy is an important key to shaping wise consumption behavior and supporting the creation of a healthy and sustainable digital economy ecosystem in Indonesia.